2017
DOI: 10.1590/s0100-736x2017000400005
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistant bacteria isolated from septic arthritis in horses

Abstract: RESUMO.-[Bactérias multirresistentes isoladas de artrite séptica equina.] Artrite séptica é uma artropatia infecciosa debilitante de equinos, que requer diagnóstico precoce e intervenção terapêutica imediata, com intuito de evitar a degeneração de a cartilagem articular e a perda da capacidade atlética e de trabalho dos animais. Poucos estu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
2
4
0
1
Order By: Relevance
“…These pathogens are related to enteric and extra-enteric (ExPEC) opportunistic infections in domestic animals, characterized by a high set of virulence factors (QUINN et al, 2011). In this study, enterobacteria represented the most common group of pathogens isolated from the synovial fluid of horses with clinical signs of arthritis, which agrees with similar studies (MOTTA, et al, 2017;SCHNEIDER et al, 1992). Enterobacteria-induced articular infections have been related to traumatic contamination of the joint with feces or environmental material and are associated with systemic dissemination (STEEL, PANNIRSELVAM & ANDERSON, 2013).…”
Section: ) ------------------------------------------------------supporting
confidence: 89%
See 1 more Smart Citation
“…These pathogens are related to enteric and extra-enteric (ExPEC) opportunistic infections in domestic animals, characterized by a high set of virulence factors (QUINN et al, 2011). In this study, enterobacteria represented the most common group of pathogens isolated from the synovial fluid of horses with clinical signs of arthritis, which agrees with similar studies (MOTTA, et al, 2017;SCHNEIDER et al, 1992). Enterobacteria-induced articular infections have been related to traumatic contamination of the joint with feces or environmental material and are associated with systemic dissemination (STEEL, PANNIRSELVAM & ANDERSON, 2013).…”
Section: ) ------------------------------------------------------supporting
confidence: 89%
“…In the current study, gentamicin, marbofloxacin, and ceftriaxone were the most effective. These findings suggested that these antimicrobials may be effective alternatives in the therapy of septic arthritis in horses, although is strongly recommended that, if possible, treatments should be based on in vitro susceptibility pattern tests (MOTTA et al, 2017). Conversely, high resistance of isolates to various drugs was reported, e.g., to erythromycin, clarithromycin, penicillin, clindamycin, streptomycin, cephalexin, amikacin, and rifampicin.…”
Section: ) ------------------------------------------------------mentioning
confidence: 99%
“…equi y Streptococcus equi subesp. zooepidemicus fueron las bacterias aisladas con mayor frecuencia en potros con artritis séptica, según Motta et al (2017).…”
Section: Discussionunclassified
“…In horses, appropriate treatment should be initiated as soon as possible, to avoid the degeneration of the articulation and synovial structures (Nix et al 1991;Morton 2005). Traditionally, systemic antibiotic therapy, joint lavage, and intra-articular administration of antibiotics are used for the treatment of septic arthritis, given that appropriate concentrations of antibiotics in the infected joint are important, so that the infection can be eliminated (Doria et al 2010;Motta et al 2017).…”
mentioning
confidence: 99%
“…Recent studies have reported high bacterial resistance in the synovial fluid of horses with septic arthritis, involving the drugs penicillin, enrofloxacin, and amikacin. Bacterial resistance to an antibiotic drug is mainly due to repeated exposure to below adequate antimicrobial concentrations (Motta et al 2017;Durha 2018). Thus, it is hypothesized that the intravenous administration of an antibiotic for the treatment of joint infections can be responsible for bacterial resistance to the drug and persistence of the disease.…”
mentioning
confidence: 99%